Problematic Issues of the Development and Implementation of the Code of Ukraine on Administrative Offenses - O. Yu. Kyrychenko (Bulletin of Kharkiv National University of Internal Affairs)
The most problematic aspects in the process of developing a new version of the Code of Ukraine on Administrative Offenses have been formulated and characterized; and the perspectives for the adoption of the Code of Ukraine on Administrative Offenses have been outlined. The main shortcoming is the obsolescence of the legal norms enshrined in the Code of Ukraine on Administrative Offenses. It has been noted that it is the reason for the massive disintegration of legislation in the specified area. Other shortcomings are the fragmentation and obsolescence of corpus delicti of administrative offenses (in this regard, it has been emphasized that currently administrative and tort law does not need to be expanded); eclecticism (combination of heterogeneous elements) of the content of substantive administrative tort legislation; inconsistency of a significant part of the misdemeanors in the field of public administration provided by the Code of Ukraine on Administrative Offenses; duplication of certain provisions of the Criminal Code of Ukraine, etc.